Intraoperative Mechanical Ventilation and Postoperative Pulmonary Complications after Cardiac Surgery. (November 2019) - Mathis, Michael R.; Duggal, Neal M.; Likosky, Donald S.; Haft, Jonathan W.; Douville, Nicholas J.; Vaughn, Michelle T.; Maile, Michael D.; Blank, Randal S.; Colquhoun, Douglas A.; Strobel, Raymond J.; Janda, Allison M.; Zhang, Min; et al.
Abstract : Background: Compared with historic ventilation strategies, modern lung-protective ventilation includes lower tidal volumes (VT ), lower driving pressures, and application of positive end-expiratory pressure (PEEP). The contributions of each component to an overall intraoperative protective ventilation strategy aimed at reducing postoperative pulmonary complications have neither been adequately resolved, nor comprehensively evaluated within an adult cardiac surgical population. The authors hypothesized that a bundled intraoperative protective ventilation strategy was independently associated with decreased odds of pulmonary complications after cardiac surgery. Methods: In this observational cohort study, the authors reviewed nonemergent cardiac surgical procedures using cardiopulmonary bypass at a tertiary care academic medical center from 2006 to 2017. The authors tested associations between bundled or component intraoperative protective ventilation strategies (VT below 8 ml/kg ideal body weight, modified driving pressure [peak inspiratory pressure − PEEP] below 16 cm H2 O, and PEEP greater than or equal to 5 cm H2 O) and postoperative outcomes, adjusting for previously identified risk factors. The primary outcome was a composite pulmonary complication; secondary outcomes included individual pulmonary complications, postoperative mortality, as well as durations of mechanical ventilation, intensive care unit stay, and hospital stay. Results: Among 4, 694 cases reviewed, 513 (10.9%) experienced pulmonary complications. After adjustment, an intraoperative lung-protective ventilation bundle was associated with decreased pulmonary complications (adjusted odds ratio, 0.56; 95% CI, 0.42–0.75). Via a sensitivity analysis, modified driving pressure below 16 cm H2 O was independently associated with decreased pulmonary complications (adjusted odds ratio, 0.51; 95% CI, 0.39–0.66), but VT below 8 ml/kg and PEEP greater than or equal to 5 cm H2 O were not. Conclusions: The authors identified an intraoperative lung-protective ventilation bundle as independently associated with pulmonary complications after cardiac surgery. The findings offer insight into components of protective ventilation associated with adverse outcomes and may serve as targets for future prospective interventional studies investigating the impact of specific protective ventilation strategies on postoperative outcomes after cardiac surgery. Abstract : In this retrospective analysis, the intraoperative ventilation bundle was associated with a lower rate of postoperative pulmonary complications. Lower modified driving pressure was independently associated with fewer pulmonary complications.Supplemental Digital Content is available in the text.